The degree of availability of critical thinking skills in the book History of the Arabs and the World An analytical study of the history of Arabs and the world - Al- Shouqairat, Ghazzi Abdullah Soulieman (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of availability of the main and subsidiary critical thinking skills in the book The History of the Arabs and the World for the eleventh grade in Jordan, the study community and its sample will be from all pages of the student book for the course of the history of Arabs and the world for the eleventh grade / literary branch. The researcher used the descriptive analytical approach to conduct the study. The study tool was represented in a content analysis card for critical thinking skills available in the book History of the Arabs and the World. The validity of the instrument was confirmed by the validity of the arbitrators. The Holsti equation was used to confirm the stability of the instrument, as the overall stability factor was 89%. Statistical processing was used by extracting iterations, percentages and ranks, and the results showed that the degree of availability of major and minor critical thinking skills in the book History of the Arabs and the World was different in terms of repetitions, percentages and ranks, where the interpretation skill came first with a total of 161 iterations and a percentage of reached 34.5%, followed by the skill of deduction in second place with a total of 126 iterations with a percentage of 27.1%, then the skill of evaluation came in third place with a total of 107 iterations and a percentage of 22.9%, then the relay skill in the fourth rank with a total of 45 repeats Ra, with a percentage of 9.7%, came in the fifth and last rank of the skill of analysis with a total of 27 iterations and a percentage of 5.8%, Consequently, all major and minor skills are included and available with the exception of sub- skill (non- acceptance of opinions that advocate historical determinism). In the light of the results, the researcher made a set of recommendations, including: taking into account the balance between the five main critical thinking skills, activating the role of teachers and educational supervisors for the History of Arabs and the World, and even involving them in setting the curriculum of history, and holding courses and training workshops for teachers of the history of Arabs and the world on employing strategies for critical thinking skills In the classroom, and redevelop teachers ’guides for the History of the Arabs and the World to include training packages dealing with learning strategies for developing critical thinking skills and how to employ them.